Evolution of morphology, magnetic properties and their relationships during sintering of barium ferite (BaFe₁₂O₁₉), cobalt ferrite (CoFe₂O₄) and cobalt nickel ferrite (Co₀.₅Ni₀.₅Fe₂O₄) - Shafie, Mohd Shamsul Ezzad (2015)
In this study, the microstructural evolution during sintering of BaM, CoF and CoNiF ferrites is reported in terms of the effects of the sintering route and temperature, as well as densification behavior and grain-growth kinetics through regression coefficient plots. Three ferrite materials were selected due to outstanding properties in electronic applications and no detail study on evolution study for that material. These materials synthesized using mechanical alloying followed by sintering from 500 to 1400°C with 100°C increments. Two sintering modes were adopted: MSS and SSS. The particle size structural, microstructural and magnetic properties details of the samples were detained by appropriate use of transmission electron microscopy (TEM), X-ray diffractometry (XRD), scanning electron microscopy (SEM), vibrating sample magnetometry (VSM), and a B-H hysteresis graph. This study proves that microstructure generally influences the magnetic properties as reflected by a threshold grain size, for the Hc, as the SD to MD magnetic transition point. At early sintering temperatures, microstructure shows widespread necking processes, proving the occurrence of densification. For hard ferrite BaM, a single phase was observed to form at a temperature of 1000°C which is higher than that for soft ferrite at 700°C. It is noted that strong magnetocrystalline anisotropy would cause significant difficulty to align magnetic moments in BaM, as indicated by Hc values for this phase. In intermediate sintering, approximately 800 to 1100°C for BaM and 700 to 1000°C for CoF and CoNiF, strong ordered magnetism is shown by the B-H loop shape. It is also believed that densification through grain boundary diffusion was dominant at this stage. Increasing sintering temperature resulted in higher density, coarser microstructure, and further densification and grain growth. However, a substantial amount of powder surface reactivity was still preserved within the microstructure of the compact. Subsequently, during the dwell time at the highest temperature, densification and grain growth took place at higher rates resulting, finally in increased density, coarser microstructure and higher initial magnetic permeability. At this stage, grain boundary diffusion through lattice and volume diffusion dominated causing microstructure to grow abnormally with introduction of intraganular pores. Porosity was observed to increase at this stage. The substitution of NiO into CoF enhances the sintering by increasing bulk diffusion due to the increased vacancy concentration which is accompanied by the solubility of Ni2+ in the ferrites. Ni2+ ions are cations that are soluble in the host lattice and enterregular positions on the tetrahedral or octahedral sites. The results for the MSS and SSS samples as obtained from their hysteresis magnetic loops, showed high saturation magnetization BaM (100 < 4πMs < 9800 G), low remanence (7 < Br, < 2039 G) and Hc (22 < Hc < 35 Oe) values. The relative density-grain size plot of the sintering process demonstrates a crossover between the densification mechanisms from grain boundary diffusion to lattice diffusion with increasing sintering temperature. Most importantly, the M-H loops for BaM, CoF and CoNiF were each found to belong to three families of M-H curves which correspond to different states of magnetism. Finally for the evolution study, it is strongly believed that there are a few factors found to sensitively influence the samples content of ordered magnetism: their ferrite-phase crystallinity degree, the fraction of grains above the critical grain size and large enough grains for domain wall accommodation.